2018
DOI: 10.1038/s41598-018-31267-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Anthesis Nitrogen Uptake and Translocation on Photosynthetic Production and Rice Yield

Abstract: Post-anthesis nitrogen uptake and translocation play critical roles in photosynthetic assimilation and grain filling. However, their effects on leaf stay-green characteristics, dry matter accumulation, and translocation after anthesis remain unclear. In this study, post-anthesis N uptake and translocation between two different rice genotypes (Yongyou12 and Zhongzheyou1) were compared through soil nitrogen leaching treatments at the meiosis stage (MST) and anthesis stage(AST) respectively, and their effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Nitrogen supplementation is important to maintain carbohydrate supply for grain ripening of indica–japonica hybrid rice 19 . In the present study, a larger reduction in grain weight was observed in YY1540 compared with that of TYHZ under the T 3 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen supplementation is important to maintain carbohydrate supply for grain ripening of indica–japonica hybrid rice 19 . In the present study, a larger reduction in grain weight was observed in YY1540 compared with that of TYHZ under the T 3 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An LI-3100C Area Meter (LI-COR, Inc., Lincoln, NE, USA) was used to measure the leaf area of each green leaf. The leaf area per square meter was calculated as the leaf area index following the method of Wu 19 . The SPAD value was determined at the maturity stage using a SPAD chlorophyII meter (SPAD-502PLUS, Spectrum Technologies, Aurora, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen accumulation and translocation, nitrogen efficiency. N content of the samples were determined using the Kjeldahl (K1100) procedure, and the accumulation and translocation of N in wheat plants were calculated as follows 22,46 :…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, photosynthesis reaches a peak after anthesis and over 70% of wheat yield is derived from photosynthesis during the period of grain growth [20,21]. Many researchers have reported that photosynthesis after anthesis is crucial determinant of yield in other crops, such as rice [22], maize [23], and soybean [24]. The contribution to photosynthesis of different leaves in the same plant can differ, and there is a difference among different crops in the contribution by functional leaves [25,26].…”
Section: Introductionmentioning
confidence: 99%